Short-term Effectiveness of High-intensity Laser Therapy in De Quervain Tenosynovitis: A Prospective, Randomized, Controlled Study - Emine DUNDAR AHI; Hulya SIRZAI2 (Medeniyet Medical Journal)
Objective: The effectiveness of high-intensity laser therapy (HILT) has been demonstrated in some musculoskeletal repetitive strain injury disorders. This study aimed to determine the short-term effectiveness of HILT in de Quervain tenosynovitis (DQT). Methods: Sixty-four patients with DQT diagnosis (32 males, 32 females; 18-65 years) were randomly divided into two groups. A short opponens splint was applied to both groups and HILT to the treatment group and sham HILT to the control group once a day, on alternate days, 3 days a week, for 5 weeks. Pre- and post-treatment evaluations were made using a visual analog scale (VAS); Quick Disabilities of the Arm, Shoulder, and Hand questionnaire; Short Form-36 Health Survey; and hand grip strength test. Results: The demographic results (age, gender, duration of complaint, body mass index, occupational group) of both groups were similar (p>0.05). The pre-treatment measured values were similar in both groups (p>0.05). After a 5-week treatment, a significant improvement was observed in all parameters in both groups. Post-treatment, hand grip strength levels were statistically higher in the HILT group than in the sham therapy group, and VAS levels were significantly lower (p<0.001). Conclusions: HILT is a non-invasive and reliable method that increases grip strength and decreases pain in DQT.